2022
DOI: 10.21203/rs.3.rs-550309/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anxiety and the associated factors among admitted surgical and medical patients, Addis Ababa, Ethiopia: A cross-sectional study

Abstract: Background Anxiety is a common comorbid mental health problem with different medical illnesses and it can complicate major medical health problems. Despite its impact of physical functioning, quality of life, drug adherence, use of health service resources, good health behaviors, and increasing suicidal tendencies and mortality, it is neither diagnosed nor treated. Therefore, this study aimed to explore the prevalence of anxiety and its determinants among admitted patients for the contribution of attempting o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…This might be a result of the significant impact that interpersonal connections have on reducing POA. POA was higher in those with weak social support than in people with strong social support, according to research from Addis Ababa, 39 which was consistent with the results of the current investigation. Social support can be associated with improved psychological readiness and decreased of fear of death.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This might be a result of the significant impact that interpersonal connections have on reducing POA. POA was higher in those with weak social support than in people with strong social support, according to research from Addis Ababa, 39 which was consistent with the results of the current investigation. Social support can be associated with improved psychological readiness and decreased of fear of death.…”
Section: Discussionsupporting
confidence: 91%
“…In the bivariable logistic regression, participants' age, sex, marital status, educational status, proposed surgery, social support, types of surgical procedures, types of anesthesia, information provision, fear of death, fear of anesthesia, fear of physical disability, absence from work, information from a negative experience, and fear of unknown were associated with POA at a p-value <0.25. Finally, after checking for multi-collinearity and controlling for potential confounders, participants' age (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45), marital status, level of social support (strong and moderate), orthopedic surgery, and fear of death remained statistically significantly associated with POA at a p-value <0.05 in multivariable analysis (Table 4). Study participants between the age of 31-45 (AOR = 0.36; 95% CI = 0.17, 0.78) were 64% less likely to develop POA than participants between the age of 18-30.…”
Section: Factors Associated With the Poamentioning
confidence: 99%
“…26 Karabulut et al 16 also reported that the level of surgical fear in geriatric surgical patients who were married was lower than in those who were single. Additionally, Tesfaw et al 27 mentioned that preoperative anxiety levels were twice as high in single individuals compared to married ones. In contrast to our study, Çınar and Bülbülo glu 19 reported no statistically significant difference between the marital status of elderly patients and their levels of surgical fear.…”
Section: Discussionmentioning
confidence: 99%